2018
DOI: 10.1108/ajim-03-2017-0063
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative information searching as learning in academic group work

Abstract: Purpose The purpose of this paper is to explore users’ learning in the collaborative information search process when they conduct an academic task as a group. Design/methodology/approach This paper presents a longitudinal study for a three-month period on an actual task. The participants, who were undergraduate students, needed to write a research proposal in three months to apply for funding for a research project, including a three-hour experiment. Findings The results show that undergraduates’ learning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 35 publications
0
16
0
3
Order By: Relevance
“…Restructuring involves constructing new structures to account for new information that LHT 38,4 conflicts with prior knowledge (Vosniadou and Brewer, 1987). In research into collaborative search processes for academic group work, learning behavior was classified as restructuring, tuning, and assimilation, and understanding topic concepts improved through the learning process (Wu et al, 2018). Bhattacharya and Gwizdka (2019) conducted a user study and found that the verbal knowledge change of participants would be reflected in their search behaviors and eye-gaze measures related to acquiring information and reading.…”
Section: Consumers'mentioning
confidence: 99%
See 1 more Smart Citation
“…Restructuring involves constructing new structures to account for new information that LHT 38,4 conflicts with prior knowledge (Vosniadou and Brewer, 1987). In research into collaborative search processes for academic group work, learning behavior was classified as restructuring, tuning, and assimilation, and understanding topic concepts improved through the learning process (Wu et al, 2018). Bhattacharya and Gwizdka (2019) conducted a user study and found that the verbal knowledge change of participants would be reflected in their search behaviors and eye-gaze measures related to acquiring information and reading.…”
Section: Consumers'mentioning
confidence: 99%
“…Various studies have investigated search as a learning process in different contexts, such as academia, and commercial planning while learning is embedded in the information searching process (Wu et al, 2018;Zhang and Soergel, 2016). A few studies have attempted to investigate potential indicators of learning and the relationship between search behavior and learning outcomes by designing learning-related search tasks (Thompson et al, 2016;Vakkari, Pannanen and Serola, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Users have been found to interact with a search system by frequently reformulating their queries to satisfy their information needs (Aloteibi and Sanderson, 2014;Jansen et al, 2000;Jansen et al, 2009). Collaborative information search (CIS) has attracted growing attention in recent years (Capra et al, 2013;Leeder and Shah, 2016;Wu et al, 2018). Collaborative search refers to an information searching and retrieving process involving human beings interacting with other humans, directly or indirectly, for solving a common task in workplace settings or everyday life situations (Hansen and Järvelin, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The first one covers the issues of collaborative information: organising, retrieval, seeking, sharing and storing (e.g. Hertzum, 2017;Mohammad Arif et al, 2015;Wu et al, 2018a). The second one refers to collaborative information: analysing, creating, editing, filtering, interpreting and synthesizing (e.g.…”
Section: Resultsmentioning
confidence: 99%